Tuning the target composition of amine-grafted CPO-27-Mg for capture of CO2 under post-combustion and air filtering conditions: a combined experimental and computational study. Issue 43 (16th October 2015) - Bernini, M. C.; García Blanco, A. A.; Villarroel-Rocha, J.; Fairen-Jimenez, D.; Sapag, K.; Ramirez-Pastor, A. J.; Narda, G. E.
Abstract : A computational and experimental study is performed to determine the optimal composition that enhances the adsorption performance at low pressure. Abstract : A computational and experimental screening of hypothetical and real compounds exhibiting different degrees of ethylenediamine grafted to the CPO-27-Mg or Mg-DOBDC skeleton is performed in order to determine the target composition that optimizes the CO2 adsorption properties under flue gas and air filtering conditions. On the basis of the [Mg2 (dobdc)] formula, eighteen hypothetical models involving 15–100% of functionalization of the coordinatively unsaturated sites (CUS) were considered by means of Grand Canonical Monte Carlo simulations to evaluate the CO2 adsorption at 298 K. In addition, post-synthesis modification was applied to CPO-27-Mg leading to three kinds of samples exhibiting 15, 50, and 60% of CUS functionalization with ethylenediamine, named CPO-27-Mg-a, CPO-27-Mg-b and CPO-27-Mg-c. Compounds were characterized using elemental analysis, TGA, FTIR spectroscopy, PXRD and DSC. Finally, bare and functionalized CPO-27-Mg materials were evaluated using gas adsorption and microcalorimetry in the 0.001–1 bar range, which is pertinent for the mentioned applications. Valuable information related to design criteria for synthesis of tuned CO2 adsorbents is derived through this computational and experimental investigation.